1998
DOI: 10.1029/98tc02206
|View full text |Cite
|
Sign up to set email alerts
|

Tectonics of the Arabian margin associated with the formation and exhumation of high‐pressure rocks, Sultanate of Oman

Abstract: Abstract. Continental crustal rocks, now structurally beneath the allochthonous Samail ophiolite, underwent blueschist to eclogite facies metamorphism prior to the emplacement of the Oman ophiolite onto the Arabian margin. The recognition of a major low angle fault within this polydeformed and polymetamorphosed sequence of metacarbonates, metabasites, quartzites and quartz mica schists greatly simplifies the interpretation of the structure and metamorphic zonation within the Saih Hatat window, NE Oman. Carphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 44 publications
3
55
0
Order By: Relevance
“…[64] The final stage of ophiolite emplacement in Oman is well documented and will not be discussed here in detail [Bechennec et al, 1988;Cawood, 1991;Gealey, 1977;Gregory et al, 1998;Miller et al, 1998;Searle and Cox, 1999]. It is noted, however, that rapid emergence of the Semail ophiolite after subduction of the Arabian continental margin is consistent with detachment of the oceanic portion of the passive plate margin (Figure 7g).…”
Section: Stage 5: Resurrectionmentioning
confidence: 94%
“…[64] The final stage of ophiolite emplacement in Oman is well documented and will not be discussed here in detail [Bechennec et al, 1988;Cawood, 1991;Gealey, 1977;Gregory et al, 1998;Miller et al, 1998;Searle and Cox, 1999]. It is noted, however, that rapid emergence of the Semail ophiolite after subduction of the Arabian continental margin is consistent with detachment of the oceanic portion of the passive plate margin (Figure 7g).…”
Section: Stage 5: Resurrectionmentioning
confidence: 94%
“…After that, many authors insisted on supra-subduction zone environment for the genesis of the Oman ophiolite [e.g., Lachize et al, 1996;Schiano et al, 1997;Searle and Cox, 1999;Shervais, 2001]. Whereas other many authors insisted that the ophiolite was produced at fast spreading ridges without subduction [e.g., Boudier et al, 1988;Juteau et al, 1988;Ernewein et al, 1988;Nicolas et al, 1988;Rochette et al, 1991;Gregory et al, 1998]. However, the original basis of the arguments for the supra-subduction zone origin, high LILE contents, has not been reexamined.…”
Section: Nature Of Magmas and Petrogenesismentioning
confidence: 99%
“…Langmuir et al [1992] showed that MORBs from different oceans have unique features, respectively (Figure 17). [Moores et al, 2000], second is that the contamination by subduction components at suprasubduction suites as claimed by Alabaster et al [1982], and third is the contamination from subduction zone which subducted opposite side of ocean ridges as present-day southern Chile Ridge [Sturm et al, 2000], because subduction beneath Arabian Platform was claimed by Gregory et al [1998]. To solve these problems, more precise and extensive works are needed.…”
Section: Nature Of Magmas and Petrogenesismentioning
confidence: 99%
“…For this reason the geological studies of the Emirates and Oman have focused on the petrological details of the ocean crust (Lippard et al 1986), and the structure and stratigraphy of the rocks below the Semail (Robertson et al 1990, Searle & Cox 1999 which record the stages of the obduction process. On the basis of these data sophisticated models for oceanic crust generation, intra-oceanic crustal detachment, partial subduction of continental crust and obduction of oceanic crust have been constructed for this region (Boudier et al 1988, Hacker et al 1996, Gnos & Nicolas 1996, Gregory et al 1998.…”
Section: Introductionmentioning
confidence: 99%